A tunable low noise high PSRR high accuracy bandgap reference using stacked-long cascode technique in 14 ​nm FinFET process. (September 2020) - Li, Qiuliang; Wu, Lei; Liu, Ran; Liu, Yi
Abstract: A tunable CMOS bandgap reference circuit is presented. To improve the match performance of the current mirror, the proposed bandgap is realized with stacked-long Cascode technique. A detailed analysis of various error sources is provided and the techniques to reduce them are discussed. The bandgap reference with an accuracy of ±1.2% from −40 ​°C to 125 ​°C draws 57μA from a 1.8 ​V supply, and occupied 0.0036 ​mm 2 in a 14 ​nm FinFET Process. The output noise is 0.76μV (rms) and the PSRR is −115dB@DC.